Implementasi Algoritma Fungsi Hash Grostl Untuk Mendeteksi Orisinalitas Citra Digital - Wahyu Satria Putra Zega; Herry Sunandar; Suginam Suginam (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Image modification is the process of manipulating part or all of the image area with the help of digital image processing techniques. Image fakes are generally difficult to analyze with the naked eye because the resulting image from the image modification process is difficult to distinguish with the naked eye. The ease of creating and changing an image can damage the credibility of the authenticity of the image in various aspects, thus making it prone to be used for criminal acts because image changes in digital images can change the information conveyed to be different. This is the basis of this research to detect the authenticity of an image. The Grostl method is a hash function to detect changes in digital images, the Grostl hash function is used to determine whether an image has been modified or not. The application of the Grostl method to generate a hash code from a digital image begins by inputting the digital image as the object to be hashed.Keywords: Image Originality, Hash, Grostl